Retrospective and Prospective Investigations about “Quatrefoil” Erythrocytes in Canine Blood Smears - Alessandra Gavazza; Marianna Ricci; Martina Brettoni; Biancaurora Gugliucci; Anna Pasquini; Daniela Rispoli; Nicola Bernabò; George Lubas (Veterinary Medicine International)
The presence of unusual two RBCs patterns (so-called “quatrefoil RBCs,” qRBCs) on canine blood smears at Optical Microscope (OM) was seen during routine evaluation of CBCs. Two consecutive retrospective investigations were arranged including about 7,000 CBCs and clinical records and laboratory data from dogs showing qRBCs. Few samples with qRBCs were prepared for Scanning Electron Microscope (SEM). qRBCs were found in 6.89% (139 of 2016) and 8.47% (133 of 1569) of dogs and in 3.89% (154 of 3,958) and 4.47% (138 of 3,081) of CBCs (some dogs were tested more than once). Statistical analysis was significant for age groups (Chi squared, P<0.0001), decreased total leukocyte and neutrophil counts (ANOVA, P<0.0001), RBCs anisocytosis, polychromasia, and Howell-Jolly bodies (ANOVA, P<0.018, <0.005, and <0.003, respectively). qRBCs were distributed in the area of feathered edge and at the smear side of body-feathered edge area in blood films. SEM ruled out the possibility of an optical illusion or an accidental overlap. qRBCs are associated with ageing of dogs, total leukocyte and neutrophil counts, and RBC anisocytosis, polychromasia, and Howell-Jolly bodies. Few hypotheses were discussed to explain the origin and meaning of this RBC arrangement.